Isolation and Characterization of Microcrystalline Cellulose and Preparation of Nano-Crystalline Cellulose from Tropical Water Hyacinth - Abdul Latif, Mohammed H.; Mahmood, Yasir Fathi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Because of the conservation problems causes by the existence of water hyacinth (W.H) as an watery plant in water bodies of Iraq, our study aimed to make use of (W.H) by isolation of microcrystalline cellulose, and a new method of preparation of Nano crystalline cellulose. Microcrystalline cellulose was produced using base bleaching method by sodium hypochlorite [NaOCl] to remove unorganized region of cellulose and lignin to create particles comprising of micro crystal and preparing of Nano crystalline cellulose from microcrystalline cellulose by acid hydrolysis and ultrasonic treatment. The Nano crystalline and microcrystalline cellulose characterized by AFM, FTIR, XRD and TGA. FT-IR spectra of microcrystalline cellules and Nano crystalline cellulose show peaks at (1076.28, 1058.92) cm-1 and (1118.71, 1112.93) cm-1 refer to the stretching vibration of C–O and stretching vibration intermolecular ester bonding. The AFM image shows that isolated microcrystalline cellulose have a diameter of (141.37 nm) and the prepared Nano crystalline have a diameter of (87.39 nm). The Thermo gravimetric analysis of cellulose showed a high decomposition temperature at (283°C) for microcrystalline cellulose and (253)°C for Nano crystalline cellulose .The thermal stability of microcrystalline cellulose was more than Nano crystalline cellulose XRD result possessed a segal crystallinity index of 92.8 % and a average crystal size of 41.7 A ° for Nano crystalline cellulose and a Segal Crystallinity Index of 86.4 % and a average crystal size of 55.3°A of microcrystalline cellulose.